2004
DOI: 10.1300/j010v38n03_06
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Stigma

Abstract: This study addressed the perceptions of stigma and disclosure behavior of HIV-seropositive mothers. Eighty-eight HIV-seropositive women in New York City completed two independent measures of stigma, the Perceived Stigma Scale and the Devaluation-Discrimination Measure. Disclosers (67%) and nondisclosers (33%) were similar in most sociodemographic characteristics-marital status, race, religion and employment, with the exception of age and education. Significant differences were found between disclosure groups i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 28 publications
2
13
1
Order By: Relevance
“…In addition, half of the existing quantitative studies had no more than 100 respondents. Measurement of disclosure practice in some studies was very general without specifics regarding the scope or approach of disclosure, such as partial disclosure/ full disclosure, forced disclosure/planned disclosure [4, 15, 17, 19, 24, 31, 3537, 40, 61]. The lack of data on these different features of disclosure might make it hard to differentiate the effects of various types of disclosure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, half of the existing quantitative studies had no more than 100 respondents. Measurement of disclosure practice in some studies was very general without specifics regarding the scope or approach of disclosure, such as partial disclosure/ full disclosure, forced disclosure/planned disclosure [4, 15, 17, 19, 24, 31, 3537, 40, 61]. The lack of data on these different features of disclosure might make it hard to differentiate the effects of various types of disclosure.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of standard measurement also made it difficult to compare results across studies. For instance, some studies reported parental disclosure rate [4, 15,19, 21, 30, 3537, 40, 41, 5961, 66], while some studies reported children’s awareness rate [3, 17, 18, 20, 24, 28, 29, 31–34, 42]. In addition, future studies should collect data from both parents and children given the potentially unique perspectives from parents and children on disclosure issues.…”
Section: Discussionmentioning
confidence: 99%
“…U.S.-based research provides support for the relevance of education (Letteney and LaPorte 2004), income (Armistead et al 2001), and maternal physical health (Armistead et al 2001;Lee and Rotheram-Borus 2002;Schrimshaw and Siegel 2002). In a sample of predominantly African American and Latina women, mothers who were less educated were more likely to disclose than more educated mothers (Letteney and LaPorte 2004).…”
Section: Introductionmentioning
confidence: 99%
“…U.S.-based research provides support for the relevance of education (Letteney and LaPorte 2004), income (Armistead et al 2001), and maternal physical health (Armistead et al 2001;Lee and Rotheram-Borus 2002;Schrimshaw and Siegel 2002). In a sample of predominantly African American and Latina women, mothers who were less educated were more likely to disclose than more educated mothers (Letteney and LaPorte 2004). In addition, African American mothers with lower incomes were more likely to disclose than those with higher incomes, perhaps due to more limited childcare options resulting in the need for children to attend doctor appointments or otherwise be present when mothers are quite ill (Armistead et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Parent–adolescent conflict broadly impacts adolescent health behaviors (Black, Ricardo, & Stanton, 1997; Dashiff, Hardeman, & McLain, 2008; Shek, 1998; Stauffer, Emerson, & Donenberg, 2006). The stresses related to stigma, compromised health, and financial burden of parental HIV could all exacerbate conflict within family relationships (Alonzo & Reynolds, 1995; Andrews, Williams, & Neil, 1993; Brown, Lourie, & Pao, 2000; Letteney & LaPorte, 2004; Reyland, Higgins-D’Alessandro, & McMahon, 2002; Rotheram-Borus, Robin, Reid, & Draimin, 1998). One might specifically hypothesize that those adolescents with adaptive coping skills, such as effective conflict resolution styles, will better manage stressful situations, such as family conflict, and therefore be less likely to engage in problem behaviors.…”
Section: Introductionmentioning
confidence: 99%